Cloning of Chicken Anaemia Virus (CUX-1) VP1 Gene Into a Lactococcus Expression Vector pMG36e - Ng, Perk Tsong (1999)
Lactococcus lactis is a non-pathogenic and non-colonising bacterium, which is being developed as a vaccine delivery vehicle for immunisation by mucosal routes. To determine whether lactococci can express the Chicken Anaemia Virus capsid protein (VP1) in immunogenic fonn, we have constructed a recombinant DNA, which constitutively expresses the VP1 as N-terminal fusion protein with Open Reading Frame-32 under the control of lactococci promoter P32 in vector pMG36e. Chicken anaemia virus (CAV) is a member of the newly categorised Circoviridae, a family of circular negative single-stranded DNA viruses. CAY VP1 gene (1.4 kb) was amplified by PCR from CAV genome which was isolated from infected Marek's disease virus transformed lymphoblastoid cell line (MDCC-MSB 1) cell lysate and cloned into pCR® 2.1-TOPO vector for sequencing. The sequenced VP1 gene, lacking its own promoter, was cloned into the lactococcal expression vector pMG36e and transformed into E. coli JM109 as the intermediate host. The recombinant plasmid was sub-cloned into L. lactis MG1363 by electroporation. Several independent verifying methods such as sequencing, Southern hybridisation and restriction enzymes analysis have confirmed the insertion of VP1 gene into pMG36e. The complete sequence of VP1 gene has 99.65% homology compared to the published CAV Cux-1 VP1 gene. A total of 5 base difference was seen to result in change of 3 amino acids sequence in the polypeptide chain. The expression of fusion protein was studied until transcriptional level. Transcription of fusion gene from strains of recombinant L. lactis MG1363 were analysed by Northern hybridisation. Northern hybridisation has detected transcription of fusion gene in recombinant L. lactis MG1363 carrying pMG36e-VP1 and produced mRNA with the size of 1.4 kb. On the basis of these results, it is concluded that the recombinant DNA pMG36e was successfully constructed in bacteria E. coli JM109 and subcloned into L. lactis MG1363. The recombinant DNA in L. lactis MG1363 is capable to express the fusion protein up to transcriptional level. Therefore, recombinant L. lactis MG1363 can be used as a potential vaccine delivery system against CAV infections.